UTILITY OF PLEURAL FLUID PROTEIN TO DIFFERENTIATE MALIGNANCY FROM TUBERCULOSIS - Sumalani, Kamran Khan; Akhter, Nousheen; Chawla, Dimple; Rizvi, Nadeem A (Journal of Ayub Medical College Abbottabad, 2025)
Background: Pleural effusion, a significant clinical problem, often poses diagnostic challenges. Tuberculosis and malignancy are the leading causes of exudative pleural effusion globally and in Pakistan. Differentiating between these two causes is essential for effective treatment, yet difficult due to overlapping clinical and biochemical profiles. Methods: This cross-sectional study was conducted at Jinnah Postgraduate Medical Center from February 2017 to May 2023, involving 603 patients with pleural effusion. It focused on exudative effusions, excluding transudative effusions, other causes, and patients with specific comorbidities. Procedures included diagnostic thoracenteses, pleural ultrasounds, biopsies, and various laboratory tests. The study aimed to assess the diagnostic utility of pleural fluid protein levels in distinguishing tuberculous from malignant effusions. Results: Out of 603 cases, 582 were analyzed. The study found significant age differences between patients with tuberculosis and malignancy. Tuberculosis was more common in younger patients, with no marked gender difference. The mean pleural fluid protein level was higher in tuberculosis (5.02±1.07 g/dL) than in malignancy (4.48±1.10 g/dL, p=0.004). A cut-off value of 5.08 g/dL for pleural fluid protein was identified as effective in differentiating between the two conditions. Conclusion: The study suggests that pleural fluid protein levels can be a valuable diagnostic marker for distinguishing between tuberculous and malignant pleural effusions. This is particularly relevant in settings where advanced diagnostic options are limited, highlighting the importance of pleural fluid analysis in clinical diagnosis.